Sosialisasi Manfaat Manajemen Keuangan Dalam Kehidupan Sehari- Hari Guna Meningkatkan Perbaikan Finansial - Kartika Sari Dewi; Ayu Puspa Lestiyadi; Tutrii . Indraswari (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2022)
This Community Service activity aims to provide socialization of the benefits of financial management in daily life in order to increase financial improvement for the employees of Pt. Crown Worldwide Indonesia. The method of activity used is to provide an explanation of how to manage finances properly. After being analyzed, we provide an explanation about managing income so that it doesn't happen where expenses are greater than income. The results of the activity show that prior to the implementation of the PKM, the staff of PT. Crown does not yet have the awareness of the importance of recording expenses and income which ultimately results in their income being depleted due to high expenses, but after the implementation of this PKM activity it is known that the participants at least have awareness and can understand that recording expenses is important because with this we can know the reality expenses every month. PKM activities play a positive role in increasing knowledge and expectations to be able to better manage employees' finances. Keywords: PKM, Finance, Income and Outcome Kata Kunci : UMKM, Biaya Produksi, Labelling